To what extent the use of reading strategies inflences reading comprehension in students from reading and conversation II course of the bachelor of arts in english emphasis in teaching, semester I 2013, of The Foreing Languaje Department of The University of El Salvador - Aquino de Ayala, Evelyn Nataly; Baires Arévalo, Santos Edith; Jovel Portillo, Marta Azucena; Gamero Ortiz, José Ricardo; Ayala,Edgar Nicolas (San Salvador, El Salvador : Universidad de El Salvador, 2013)
When a non-native English speaker is trying to learn the language, a major component in doing so is reading. Throughout the entire duration of their studies, students from the Foreign Languages Department experience the great necessity not only to read texts in different subjects, but also to comprehend the different types of readings presented. For that reason, it is necessary to explore the different strategies that students need in order to enhance their reading comprehension and reading skills. Therefore, this research was focused on useful reading strategies that students implement to improve their reading comprehension skills. The purpose of the research was to know if reading strategies play an important role to get better comprehension in the different types of readings that students from the Foreign Languages Department of the University of El Salvador encounter during the whole process of learning English. Furthermore, another purpose for this research was to analyze the difficulties that English language students encounter while reading various subjects during the period of their studies.
Incluye anexos.
Tesis para optar al título de -- (Licenciatura en Idioma Inglés Opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2013
Bibliográfia : hoja 66
Keywords: Inglés -- Enseñanza